1984
DOI: 10.2134/agronj1984.00021962007600050008x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Effects on Seed Yield, Growth, and Germination of Grain Sorghum1

Abstract: Grain sorghum (Sorghum bicolor (L.) Moench) is grown on saline soils in the western United States. Because of the lack of information on salinity effects on seed yield, a field plot study was conducted. Six saline treatments were imposed on a Holtville silty clay (clayey over loamy montmorillonitic (calcareous), hyperthermic Typic Torrifluvents) by irrigating with waters that were salinized with NaCl and CaC1 2 (1:1 by wt). The electrical conductivities of the irrigation waters were 1.5, 2.7, 5.0, 7.4, 9.8, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
1
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 4 publications
11
44
1
3
Order By: Relevance
“…The EC5012 of 21 .2 dSm 1 value obtained for our materials indicates lower average tolerance for this character than previously reported in the literature for grain sorghum . Lyles & Fanning (1964) and Francois et al . (1984) reported that soil salinity only affected emergence above a threshold equivalent to 22 dSm -1 , but those studies were limited to one and two commercial hybrids, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…The EC5012 of 21 .2 dSm 1 value obtained for our materials indicates lower average tolerance for this character than previously reported in the literature for grain sorghum . Lyles & Fanning (1964) and Francois et al . (1984) reported that soil salinity only affected emergence above a threshold equivalent to 22 dSm -1 , but those studies were limited to one and two commercial hybrids, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies on related cereals (meadow foxtail) have indicated that foxtail millet is moderately sensitive to salinity (Maas 1993). The salt concentration (100 mM NaCl resulting in a soil ECe of 11.2 ± 0.28 dS m -1 in an Alfisol) chosen for screening, was similar to the ones used in some previous studies for sorghum ; Maas 1985; Francois et al 1984;El-Haddad and O'Leary 1994;Igartua et al 1995). Later works (Islam et al 2011) also confirmed that saturating with 100 mM salt solution would be the most suitable for good genetic discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…In both 2008 and 2009, half of the pots were artificially salinized by applying a dose of 1.08 g NaCl kg -1 , equivalent to applying a 100 mM solution of NaCl in sufficient volume (2.035 L) to wet the Alfisol precisely to field capacity (19.7% w/w). A salt concentration of 100 mM NaCl was chosen for this screening as this was similar to the one used in some successful previous studies with sorghum (Maas 1985;Francois et al 1984;El-Haddad and O'Leary 1994;Igartua et al 1995) and recently for foxtail millet causing a plant biomass loss of 37% (Islam et al 2011). The remaining pots received tap water containing no significant amount of NaCl in the same quantities to bring them to field capacity.…”
Section: Plant Growth Treatment Conditions Sowing Dates and Geneticmentioning
confidence: 99%
“…Calcium chloride treatment, which commenced 18 days after transplanting and lasted for 5 weeks, was done by dissolving each treatment amount in 1 litre of distilled water (Francoise et al,, 1984). The entire experiment was repeated two times.…”
Section: Methodsmentioning
confidence: 99%